My branch is your branch: Talar morphology correlates with relative substrate size in platyrrhines at Tiputini Biodiversity Station, Ecuador. Issue 133 (August 2019) - Boyer, Doug M.; Yapuncich, Gabriel S.; Dunham, Noah T.; McNamara, Allison; Shapiro, Liza J.; Hieronymus, Tobin L.; Young, Jesse W.
Abstract: Given that most species of primates are predominantly arboreal, maintaining the ability to move among branches of varying sizes has presumably been a common selective force in primate evolution. However, empirical evaluations of the relationships between morphological variation and characteristics of substrate geometry, such as substrate diameter relative to an animal's body mass, have been limited by the lack of quantified substrate usage in the wild. Here we use recently published quantitative data to assess the relationships between relative substrate size and talar morphology in nine New World monkey species at the Tiputini Biodiversity Station, Ecuador. Within this sample, both fibular facet angle (the angle between the fibular facet and the trochlear rims) and body-mass-standardized area of the medial tibial facet decrease as average and maximum relative substrate size increases. Correlations between medial tibial facet area and relative substrate size are driven by the inclusion of callitrichids in this sample. Nevertheless, these findings strengthen the hypothesis that variation in fibular facet orientation and medial tibial facet area are functionally correlated with habitual degrees of pedal inversion. They also strengthen the notion that evolutionarily changing body mass could impact habitat geometry experienced by a lineage and thereby substantially impact major trends in primate morphological evolution. This study highlights the importance of empirical data on substrate use in living primates for inferring functional and evolutionary implications of morphological variation.